Perlindungan Hukum Terhadap Pengguna Aplikasi E-Commerce yang Terdampak Kebocoran Data Pribadi - Maldi Omar Muhammad; Lucky Dafira Nugroho (LPPM Universitas Trunojoyo Madura, 2021)
Technological developments continue to develop very rapidly, one of which is in the electronic trading system, hereinafter referred to as e-commerce. Along with this, there are concerns from E-Commerce application media users regarding personal data stored by E-Commerce application media companies, so that more specific rules are needed regarding legal protection for E-Commerce application users. The purpose of this research is to further review the rules related to legal protection for users who are affected by the leakage of personal data on E-Commerce media such as based on the agreement in the Terms and Conditions as well as the rules of related laws such as, the ITE Law and its amendments, PP 71/2019 concerning the Implementation of Electronic Systems and Transactions, Government Regulation Number 80 of 2019 concerning Trading Through Electronic Systems, Regulation of the Minister of Communication and Information Technology Number 20 of 2016 concerning Protection of Personal Data in Electronic Systems. The method used in this research is normative juridical research, with a statutory approach. The collection of sources of legal materials, both primary and secondary, is carried out through laws and regulations and all official documents that contain legal provisions and searches related to research results such as journals and the internet.